Does emotion affect distance learning students' satisfaction during the COVID-19 lockdown?. (19th May 2023) - Musella, Flaminia; Guglielmetti Mugion, Roberta; Zanda, Stefania; Renzi, Maria Francesca
Abstract : Due to the COVID-19 outbreak, traditional teaching paradigms have been suffering a deep change set that will be completed once a new social balance will be reached. In this period, many students have been emotionally shocked due to the rude and fast passage from traditional to remote teaching. The main assumption of this study is that emotions may directly affect students' learning capability and their satisfaction by possibly modifying relations between satisfaction and its drivers. This understanding is crucial since satisfaction also affects students' learning performance. The paper aims at discussing the role of emotions in the relations between satisfaction and its drivers. The focus is on higher education. During the first Italian lockdown, an online survey was carried out, involving 178 students of a Roma Tre University master's degree, identifying a model for exploring a new concept of students' emotional satisfaction.